Forced convection heat transfer of polymer melt flow inside channels with contraction/expansion sections - Vaz M.* (2011)
Polymer melt flow inside channels with contraction/expansion sections is commonly found in numerous forming applications. Due to high polymer viscosity, this flow presents laminar behaviour, high pressure drop and relevant viscous heating effect. The analysis presented in this work comprises the numerical simulation of a set of equations (mass, linear momentum and energy conservation principles) that models this class of flow. The generalized Newtonian formulation is employed, being the apparent polymer viscosity computed as a function of temperature and shear strain rate. The governing equations are discretized using the finite difference method with central formulae (for both diffusion and convection terms). The work is focused on the assessment of the local and global Nusselt numbers based upon a parametric study of the effects of the contraction/expansion aspect ratio and entrance flow velocity. The main findings indicate that, similarly to Newtonian flows, the Nusselt number presents a good correlation with Reynolds, Prandtl and Eckert numbers. © 2011 Elsevier Ltd.